Correlation of LMP-1 expression with KRAS and Cyclin-D1 expressions in WHO type III NPC patients - Neri, Rizki Amelia Yurika; Soehartono, Soehartono; Surjotomo, Hendradi (PERHATI-KL, 2024)
Background: Nasopharyngeal carcinoma (NPC) is a malignancy with pathologically andepidemiologically unique characteristics. The risk factors that are often associated with NPC are chronicEBV infection, environmental factors, and epigenetic changes. EBV infection expresses Latent MembraneProtein-1 (LMP-1) in NPC. The role of LMP-1 is to activate signaling pathways, including KRAS-RAFMEK-ERK which induces transcription of cyclin D1 that contributes to cell proliferation. Purpose: Todetermine the correlation between LMP-1 expression and KRAS expression, LMP-1 expression with cyclinD1 expression, and KRAS expression with cyclin D1 expression in nasopharyngeal tissue of WHO typeIII NPC patients. Method: Analytical observational study with a cross-sectional approach involving 30paraffin blocks of biopsy tissue from NPC patients who had not received radiotherapy or chemotherapy.Expression of LMP-1, KRAS, and cyclin D1 was examined with immunohistochemical staining methodand calculated using manual counting by anatomical pathologists. Result: Statistical analysis of LMP-1expression with KRAS expression showed an insignificant positive correlation (p=0.546) with a correlationcoefficient (ρ=0.115). The LMP-1 expression with cyclin D1 expression showed an insignificant positivecorrelation (p=0.305) with a correlation coefficient (ρ=0.194). The KRAS expression with cyclin D1expression showed an insignificant positive correlation (p=0.262) with a correlation coefficient (ρ=0.212). Conclusion: In WHO type III NPC tissue in the proliferative process, an increase in LMP-1 expression(53.4%±27.35%,) was followed by an increase in KARS expression (49.83%±22.83%) and D1 expression(42.27%±31.94%) as well as an increase in KRAS expression (42.27%±31.94%) followed by an increasein cyclin D1 expression (42.27%±31.94%) although not significant.